Expression of hydrogenase in Alcaligenes spp. is altered by interspecific plasmid exchange. - Friedrich, B (1984)
Alcaligenes hydrogenophilus was found to contain a soluble and a particulate hydrogenase whose control and structure differed in part from that in Alcaligenes eutrophus. One of at least two plasmids indigenous to A. hydrogenophilus determines hydrogenase genes (Hox). The interspecific exchange of Hox-encoding plasmids generated transconjugants which expressed the structural and regulatory Hox phenotype of the donor.